Stromal Expression of CD10 in Invasive Breast Carcinoma and Its Correlation with ER, PR, HER2-neu, and Ki67 - Vandana Puri; Manjula Jain; Shaji Thomas (International Journal of Breast Cancer)
CD10 is a cell surface zinc-dependent endopeptidase, which degrades many bioactive peptides. CD10 expression in tumour stroma is associated with biological aggressiveness of many epithelial malignancies. To date, only one study has correlated with expression of CD10 with well-known prognostic markers of breast, that is, ER, PR, HER2-neu, and tumour grade; however, its correlation with ki67 is still not studied. The aim of this study is to evaluate stromal CD10 expression in breast carcinoma and to examine its correlation with ER, PR, HER2-neu, and Ki67. Methods and Results. CD10 expression in fifty patients was assessed by immunohistochemistry and scored as negative, weak and strong. CD10 was found to be positive in stroma of 40/50 (80%) cases. Stromal CD10 showed positive correlation with tumour grade, HER2-neu (P=.000), and ki67 (P=.027), negative correlation with ER and PR. Conclusions. Hence CD10 expression correlated strongly with well-established negative prognostic markers, that is, HER2-neu and ki67 positivity, ER/PR negativity, and higher tumour grade, thus indicating that CD10 can be used as independent marker indicating poor prognosis and can be used as target for the development of novel therapies.